Marfan syndrome in children: correlation between musculoskeletal features and cardiac Z-score. Issue 3 (11th September 2020) - De Maio, Fernando; Pisano, Calogera; Caterini, Alessandro; Bertoldo, Fabio; Ruvolo, Giovanni; Farsetti, Pasquale
Abstract : We investigated the correlation between the musculoskeletal features and the cardiovascular anomalies in pediatric patients affected by Marfan syndrome, in order to identify possible orthopedic deformities that could be a warning sign for severe aortic dilatation. Moreover, we analyzed the role of the orthopedic aspects in the early diagnosis of the disease in a pediatric population. Seventy-two patients from 3 to 14 years of age, underwent interdisciplinary evaluation that included an orthopedic and cardiological examination. At the orthopedic examination, we analyzed the musculoskeletal features included in the systemic score of the revised Ghent criteria. Cardiological evaluation included a transthoracic echocardiography with definition of the cardiac Z-score, which is an index that evaluates aortic diameter. A statistical analysis was performed. We identified a statistically significant correlation between the presence of pectus excavatum and cardiac Z-score ≥3 ( P = 0.022). Clinically, this data means that pectus excavatum is frequently observed in patients with larger aortic root diameter. On the contrary, no statistically significant correlation was found between the other investigated musculoskeletal features and a pathological Z-score. In the pediatric population, the diagnosis of Marfan syndrome remains difficult because many clinical manifestations are age-dependent and the Ghent criteria, usually used for adults, are not reliable in children. Our results show that the presence of pectus excavatum could help in the early identification of patients at greater risk of developing possibly fatal aortic disease. However, it is always indicated to screen all patients with Marfan syndrome for cardiac abnormalities, even in absence of pectus excavatum.